Objective Sleep Interruption and Reproductive Hormone Dynamics in the Menstrual Cycle - Sharkey, Katherine M. (2014)
OBJECTIVES: Women report greater sleep disturbance during the premenstrual phase of the menstrual cycle and during menses. However, the putative hormonal basis of perceived menstrual cycle related sleep disturbance has not been investigated directly. We examined associations of objective measures of sleep fragmentation with reproductive hormone levels in healthy, premenopausal women. METHODS: 27 women with monthly menses had hormone levels measured at two time points during a single menstrual cycle: the follicular phase and the periovulatory to mid-luteal phase. A single night of home polysomnography (PSG) was recorded on the day of the periovulatory/mid-luteal phase blood draw. Serum progesterone, estradiol, and estrone levels concurrent with PSG and rate of change in progesterone (PROGslope) from the follicular blood draw to PSG were correlated with log-transformed wake after sleep onset (lnWASO%) and number of wakes/hour of sleep (lnWake-Index) using linear regression. RESULTS: Sleep was more fragmented in association with a steeper PROGslope (lnWASO% p=0.016; lnWake-Index p=0.08) and higher concurrent estrone level (lnWASO% p=0.03; lnWake-Index p=0.01), but the effect of estrone on WASO was lost after accounting for PROGslope. WASO% and Wake-Index were not associated with concomitant progesterone or estradiol levels. CONCLUSIONS: A steeper rate of rise in progesterone levels from the follicular phase through the mid-luteal phase was associated with significantly greater WASO, establishing a link between reproductive hormone dynamics and sleep fragmentation in the luteal phase of the menstrual cycle.